Management and teaching experience in a new Vocational Integrated School - Fombona Cadavieco, Javier (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
Integrated Vocational Training Schools are new institutions, which meet diverse educational levels and subsystems. They combine continued and occupational education with official teaching and training equivalent to Secondary School Education Centres, as well as other innovative activities such as the evaluation and certification of professional competencies according to the National System for Professional Qualifications. This article will delve into the successful and innovative process of the administration at the Integrated Vocational Training Centre for Communication, Media and Sound in Langreo, following its development as a leading institution in the framework of the public education in Asturias (Spain).